Growth conditions of tree species relative to climate change and sea level rise in low-lying Mid Atlantic coastal forests - Haaf, LeeAnn; Dymond, Salli F. (Frontiers in Forests and Global Change, 2024)
Introduction Coastal forests occupy low-lying elevations, typically adjacent to tidal salt marshes. Exposed to increased flooding with sea level rise, coastal forests have retreated as salt marshes advance upslope. Coastal forests likely currently experience periodic tidal flooding, but whether they temporarily accommodate or quickly succumb to rising sea level under changing climatic conditions remains a complex question. Disentangling how tidal flooding and climate affect tree growth is important for gauging which coastal forests are most at risk of loss with increasing sea levels. Methods Here, dendrochronology was used to study tree growth relative to climate variables and tidal flooding. Specifically, gradients in environmental conditions were compared to species-specific (Pinus taeda, Pinus rigida, Ilex opaca) growth in coastal forests of two estuaries (Delaware and Barnegat Bays). Gradient boosted linear regression, a machine learning approach, was used to investigate tree growth responses across gradients in temperature, precipitation, and tidal water levels. Whether tree ring widths increased or decreased with changes in each parameter was compared to predictions for seasonal climate and mean high water level to identify potential vulnerabilities. Results These comparisons suggested that climate change as well as increased flood frequency will have mixed, and often non-linear, effects on coastal forests. Variation in responses was observed across sites and within species, supporting that site-specific conditions have a strong influence on coastal forest response to environmental change. Discussion Site- and species-specific factors will be important considerations for managing coastal forests given increasing tidal flood frequencies and climatic changes.